From Monocentric to Pluricentric Approach in Speaking Class: Exploring Accent Acceptance among Indonesian Pre-service English Teachers - Sutarno, Sutarno; Fitriati, Sri Wuli; Trisanti, Novia (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Previous research has examined EFL learners' perceptions of diverse accents. However, research focusing on the perspectives of Indonesian English teacher candidates is still rare, particularly in the context of speaking classrooms, where identities associated with accents are most prominent.This qualitative case study investigates the impact of a pluricentric teaching approach on the attitudes and speaking confidence of Indonesian pre-service English teachers. Within Indonesia's vast ELT context, where monocentric, native-speaker ideologies often prevail, pre-service teachers frequently experience significant anxiety and linguistic insecurity regarding their own accents and comprehension of diverse English varieties. This study explores how implementing a pluricentric framework which validates diverse English accents and prioritizes intelligibility over native-like pronunciation in an academic speaking course influences these perceptions. Data was collected through semi-structured interviews with five purposively selected pre-service teachers. Thematic analysis revealed three pivotal findings. First, the pluricentric method catalyzed a profound shift in attitudes, moving participants from frustration and anxiety towards an appreciation and normalization of accent diversity. Second, a strong, symbiotic relationship was identified between increased accent acceptance and growth in speaking confidence, facilitated by the mitigation of